LAND RESOURCES AND EFFICIENCY OF THEIR USE IN AGRICULTURE (World Bulletin of Public Health, 2023)
The article, the effective use of land resources in agriculture on a scientific, economic and geographical basis, studies the general situation of the use of land resources in Uzbekistan, including identifying ways to solve existing problems in the use of land resources. in regional agriculture and specific ways to eliminate them, practical recommendations and proposals have been developed.